1974
DOI: 10.1029/wr010i003p00597
|View full text |Cite
|
Sign up to set email alerts
|

Reverse flow routing by the implicit method

Abstract: The concept of ‘reverse’ flow routing in rivers is proposed, in which upstream flow hydrographs are specified from a downstream flow requirement. An example is given of reverse flow routing by the implicit method of solution of the equations of momentum and continuity. Reverse flow routing is further described in the context of the x‐t plane, and then the point is made that solutions were not found in all possible directions of computation in the x‐t plane. Solutions were found only in the directions of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Eli et al (1974), Szymkiewicz (1993) and Bruen and Dooge (2007) approached this inverse problem on the basis of the equations of St. Venant, which they inverted via direct reverse-routing (finite differences); the procedure was found to be sensitive (oscillations) to the discretisation parameters and to the channel bed slope and wave frequency, collapsing fairly rapidly at low slopes and/or high frequencies. Koussis et al (2012) reoriented the Muskingum routing scheme to step back sequentially; they found also in this case grid design to be important, although that routing scheme is more robust than reverse solvers of the St. Venant equations.…”
Section: Reverse Routing Of Flood Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eli et al (1974), Szymkiewicz (1993) and Bruen and Dooge (2007) approached this inverse problem on the basis of the equations of St. Venant, which they inverted via direct reverse-routing (finite differences); the procedure was found to be sensitive (oscillations) to the discretisation parameters and to the channel bed slope and wave frequency, collapsing fairly rapidly at low slopes and/or high frequencies. Koussis et al (2012) reoriented the Muskingum routing scheme to step back sequentially; they found also in this case grid design to be important, although that routing scheme is more robust than reverse solvers of the St. Venant equations.…”
Section: Reverse Routing Of Flood Wavesmentioning
confidence: 99%
“…Reverse routing is an ill-posed, inverse problem on which few publications have appeared since the contribution of Eli et al (1974). Eli et al (1974), Szymkiewicz (1993) and Bruen and Dooge (2007) approached this inverse problem on the basis of the equations of St. Venant, which they inverted via direct reverse-routing (finite differences); the procedure was found to be sensitive (oscillations) to the discretisation parameters and to the channel bed slope and wave frequency, collapsing fairly rapidly at low slopes and/or high frequencies.…”
Section: Reverse Routing Of Flood Wavesmentioning
confidence: 99%
“…Floods are substantial natural hazards worldwide due to their destructive impacts on societies and the resulting economic losses [1][2][3][4]; flood management is even more critical for decreasing the disastrous effects [5][6][7][8][9][10] in real-life problems in developing countries such as Turkey [11], China [12,13], and Malaysia [14,15], as well as developed countries such as the USA [16] and Italy [17]. Practical flood management strategies include upstream adjustments [18][19][20], flood defense infrastructure [21][22][23][24], and downstream substructures [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Ferrari et al: Discharge hydrograph estimation at upstream-ungauged sections reverse form of the Saint Venant equations (e.g. Eli et al, 1974;Szymkiewicz, 1993;Dooge and Bruen, 2005;Bruen and Dooge, 2007) and the back-oriented application of hydrological routing schemes (e.g. Das, 2009;Koussis et al, 2012;Koussis and Mazi, 2016).…”
Section: Introductionmentioning
confidence: 99%